2018
DOI: 10.1055/s-0044-100722
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Improves Painful Diabetic Neuropathy by Suppressing the Expression and Activity of Voltage-Gated Sodium Channel in Rat Dorsal Root Ganglia

Abstract: Painful diabetic neuropathy (PDN) is one of the intractable complications of diabetes mellitus, which manifest as exaggerated pain perception. Previous studies showed that Tanshinone IIA (TIIA), one of the major bioactive extracts of Salvia miltiorrhiza Bunge, have obvious analgesic effect on different types of pain process, and the underlying analgesic mechanisms are not fully understood. The present study combined the behavioral, electrophysiological and biochemical methods to elucidate the analgesic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, cryptotanshinone displayed antinociception in chronic constriction injury-induced neuropathic pain in rats [ 30 ]. Additionally, tanshinone IIA improved diabetic neuropathy [ 31 ]. Moreover, tanshinones from SM could revert the chemotherapy-induced neuropathy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cryptotanshinone displayed antinociception in chronic constriction injury-induced neuropathic pain in rats [ 30 ]. Additionally, tanshinone IIA improved diabetic neuropathy [ 31 ]. Moreover, tanshinones from SM could revert the chemotherapy-induced neuropathy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of hypoxia in the endometrium, neuroischaemia, the loss of neurotrophic support, and neurological dysfunction are observed [34]. Studies have shown that a variety of mechanisms, such as adrenergic mechanisms, Na1 currents, opioid neurotransmission and oxidative stress, are involved in the neuropathic pain response in DPN [35][36][37]. In recent years, many researchers have focused on oxidative stress in peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In rat STZ-induced neuropathic pain, tanshinone II A significantly improved mechanical allodynia and thermal hyperalgesia. Through electrophysiological and biochemical methods, it was elucidated that tanshinone II A normalized the altered activity of primary sensitive neurons by lowering the enhanced TTX-R and TTX-S sodium channel currents [ 195 ]. In mouse oxaliplatin-induced neuropathic pain, 7-day repeated p.o.…”
Section: Active Antinociceptive Principlesmentioning
confidence: 99%